Effect of Derivative Usage on Firm Risk An Empirical Research on US Firms - Zhang, Hehuizi (2018)
After the 2008 Global Financial Crisis, risk management has played an increasingly important role in daily operations of many worldwide corporations. Financial derivatives that are often considered effective risk management instruments are broadly used by many companies. The objective of this paper is to examine the effect of derivative usage on total risk, systematic risk, idiosyncratic risk and cash flow volatility based on 494 non-financial US companies from 2012 to 2017.